ANAK-ANAK TERANCAM PUTUS SEKOLAH DI JORONG MUDIK SIMPANG KABUPATEN PASAMAN BARAT PROVINSI SUMATERA BARAT - Agustina Rahmi; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at Jorong Mudik Simpang Kenagarian Kajai West Pasaman Talamau subdistrict of West Sumatra. This research aims to analyze the role of the Community (family, school, peers) in providing pressure against dropping out of school or not to school dropout. Sample determination techniques generally purposive sampling because the Researcher has determined several criteria subject to use as a source of information in research 1 Person key informant, the informant and 5 people 6 people triangulation. Data analysis was done using descriptive qualitative and instrument data are observation, interview and documentation. The results of this study indicate that the causes of dropouts and the factors that provide a threat to economic conditions, namely the desire itself, environmental factors and influence to peers. The environment is still at domination by the community or children who do not attend school and have a less knowledge will make the education of children who are still driven to school dropouts. The role of the community that always runs in the community will determine the attitude and the future of the child and of any community will generate cost and reward the actions that set the child either being dropouts or remain in school.Keywords: Endangered Dropouts, Community Roles, Jorong Mudik Simpang